1984
DOI: 10.1159/000242006
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Urine Amino Acid Patterns during the First Month of Life in Small-for-Date Infants

Abstract: Prenatal nutrition is impaired in small-for-gestational-age infants. Serum amino acids may show some biochemical features related to the nutritional state of these children. We have carried out a study on serum and urine amino acids in 12 small-for-date infants (SFD) and 14 healthy newborns from birth to 1 month of life. SFD infants showed a high serum level of alanine and decreased concentrations of branched chain amino acids, aspartate, cystine and tryptophan at birth. The results are compatible with a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The concentration of cysteine in plasma was not determined. These observations are worthy of further investigation because various infant formulas differ in their quantity of total protein (Robles, 1984;Janas, 1985).…”
Section: Metabolismmentioning
confidence: 88%
“…The concentration of cysteine in plasma was not determined. These observations are worthy of further investigation because various infant formulas differ in their quantity of total protein (Robles, 1984;Janas, 1985).…”
Section: Metabolismmentioning
confidence: 88%
“…SGA infants are more sensitive to metabolic imbalances than AGA infants (Baserga et al 2004). Also, Robles et al (1984) reported hypertyrosinemia in small-for-date (SFD) infants. Hypertyrosinemia results from immature function of the enzyme 4-hydroxyphenylpyruvate dioxygenase, most frequently in premature infants (Russo et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In neonates with intrauterine growth retardation, biochemical abnormalities similar to those of protein malnutrition have been noted (e.g., reduction in serum albumin and significant changes in the plasma amino acid profile). When these infants were provided with protein in quantities of about 4 g/kg/day, the biochemical indices of malnutrition normalized without any manifestation of metabolic ill effects [11,12]. Kashyap et al [13] showed that when protein intake from milk-based formula was 3.8 g/kg/day, gains in weight and length of low birth weight infants (^1,750 g) were greater than when it was 2.8 g/kg/day, although the difference did not reach statistical significance probably due to small sample size (14 infants in low protein intake group versus 15 infants in high protein intake group).…”
Section: Introductionmentioning
confidence: 99%